Bluetooth application developer's guide : the short range interconnect solution - Krammer, David (London : Syngress Media, 2002)
"Bluetooth (enabled devices) will ship in the billions of units once it gains momentum."--Martin Reynolds, Gartner GroupBluetooth is the most exciting development in wireless computing this decade! Bluetooth enabled devices can include everything from network servers, laptop computers and PDAs, to stereos and home security systems. Most Bluetooth products to hit the market in 2001 will be PC cards for laptop computers and access points, which allow up to seven Bluetooth devices to connect to a network. Reports indicate that by the end of 2003 there will be over 2 billion Bluetooth-enabled dev